Targeted Redox Regulation α-Ketoglutarate Dehydrogenase Complex for the Treatment of Human Diseases - Ryan J. Mailloux (Cells)
α-ketoglutarate dehydrogenase complex (KGDHc) is a crucial enzyme in the tricarboxylic acid (TCA) cycle that intersects monosaccharides, amino acids, and fatty acid catabolism with oxidative phosphorylation (OxPhos). A key feature of KGDHc is its ability to sense changes in the redox environment through the reversible oxidation of the vicinal lipoic acid thiols of its dihydrolipoamide succinyltransferase (DLST; E2) subunit, which controls its activity and, by extension, OxPhos. This characteristic inculcates KGDHc with redox regulatory properties for the modulation of metabolism and mediating of intra- and intercellular signals. The innate capacity of KGDHc to participate in the regulation of cell redox homeodynamics also occurs through the production of mitochondrial hydrogen peroxide (mtH2O2), which is generated by the dihydrolipoamide dehydrogenase (DLD; E3) downstream from the E2 subunit. Reversible covalent redox modification of the E2 subunit controls this mtH2O2 production by KGDHc, which not only protects from oxidative distress but also modulates oxidative eustress pathways. The importance of KGDHc in modulating redox homeodynamics is underscored by the pathogenesis of neurological and metabolic disorders that occur due to the hyper-generation of mtH2O2 by this enzyme complex. This also implies that the targeted redox modification of the E2 subunit could be a potential therapeutic strategy for limiting the oxidative distress triggered by KGDHc mtH2O2 hyper-generation. In this short article, I will discuss recent findings demonstrating KGDHc is a potent mtH2O2 source that can trigger the manifestation of several neurological and metabolic diseases, including non-alcoholic fatty liver disease (NAFLD), inflammation, and cancer, and the targeted redox modification of the E2 subunit could alleviate these syndromes.